Implementation of Finger Painting Method to Improve Children's Creativity in the Development of Children's Fine Motor Skills in Group ARA Nurul Huda NW Banjarsari - Zulfia, Herni; Ismayadi, Ismayadi (JUPE : Jurnal Pendidikan Mandala, 2025)
The research entitled Implementation of Finger Painting Method to Improve Children's Creativity in the Development of Children's Fine Motor Skills in Group A RA Nurul Huda NW Banjarsari The formulation of the problem in this study is: How are the Efforts to Improve Children's Fine Motor Creativity Through Finger Painting Activities at RA Nurul Huda NW Banjarsari?. The research conducted aims to determine the Efforts to Improve Children's Fine Motor Creativity Through Finger Painting Activities at RA Nurul Huda NW Banjarsari. The type of research that the researcher will use is Classroom Action Research (CAR) or another name, namely Classroom Action Research. The classroom action research planned in this study is the implementation of the experimental method which is carried out in two cycles consisting of 4 stages, namely planning, action, observation and reflection. The results are as follows: 1. Pre-cycle activities with the results of the Aspect being able to choose and adjust colors to draw objects with a value of 31%. The aspect of being able to coordinate the eyes and hands when drawing with fingers with a value of 42%. The aspect of being able to produce good results from painting using fingers with a value of 27%. 2. Cycle 1 activities with the results of Aspects being able to choose and adjust colors to draw objects at the 1st meeting with 31%, the 2nd meeting with a value of 37%, and the 3rd meeting with a value of 46%. Aspects being able to coordinate eyes and hands when drawing with fingers at the 1st meeting with 30%, the 2nd meeting with a value of 37%, and the 3rd meeting with a value of 40%. Aspects being able to produce good works of painting using fingers at the 1st meeting with 30%, the 2nd meeting with a value of 36%, and the 3rd meeting with a value of 41%. 3. Cycle 2 activities with the results of Aspects being able to choose and adjust colors to draw objects at the 1st meeting with 50%, the 2nd meeting with a value of 62%, and the 3rd meeting with a value of 81%. Aspects being able to coordinate eyes and hands when drawing with fingers at the 1st meeting with 51%, the 2nd meeting with a value of 62%, and the 3rd meeting with a value of 80%. The aspect of being able to produce good results from finger painting at the 1st meeting with 50%, the 2nd meeting with a value of 59%, and the 3rd meeting with a value of 80%.